2018
DOI: 10.3390/polym10010076
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Micellar and Solubilizing Behavior of Three EO-PO Based Star Block Copolymers Varying in Hydrophobicity and Their Application for the In Vitro Release of Anticancer Drugs

Abstract: Abstract:The temperature and pH dependent self-assembly of three star shaped ethylene oxide-propylene oxide (EO-PO) block copolymers (Tetronics ® 304, 904 and 908) with widely different hydrophobicity was examined in aqueous solutions. Physico-chemical methods viz. viscosity, cloud point, solubilization along with thermal, scattering and spectral techniques shows strongly temperature and salt dependent solution behavior. T304 possessing low molecular weight did not form micelles; moderately hydrophilic T904 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Tetronics (poloxamines) possess X-shaped structure which consists of chains of PPO–PEO blocks linked to central ethylene diamine group, the tertiary amine central groups has a major task regarding the thermodynamic stability of Tetronics (Vyas et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tetronics (poloxamines) possess X-shaped structure which consists of chains of PPO–PEO blocks linked to central ethylene diamine group, the tertiary amine central groups has a major task regarding the thermodynamic stability of Tetronics (Vyas et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The solubilization efficiency of the drug into the BCP micelles depends on the compatibility between the drug and micellar core of polymers, while the drug release depends on the localization of the drug into the micelle. Studies have reported that the hydrophobicity of BO blocks is six times greater than the PO blocks in commercially available Pluronics and Tetronics. , Hence, BO blocks show better compatibility with hydrophobic anticancer drugs. In our study, the released profile of curcumin and quercetin in 5%w/v 39–47–39 was examined for suitable application in a sustainable release.…”
Section: Resultsmentioning
confidence: 99%
“…A series of more hydrophobic BCP counterparts with a similar architecture but with the replaced PO segment by a more hydrophobic poly­(butylene oxide) (BO), poly­(styrene oxide), or phenylglycidyl ether have been proposed. Among them, special attention has been paid to the BCP with 1,2-butylene oxide (BO) as the hydrophobic block which is demonstrated to be “biologically active”. Such behavior is attributed to the superior hydrophobicity of the BO block compared to PO (about sixfold as estimated from the ratio of the logarithms of the molar cmc). This enables the micellization at much lower copolymer concentrations which make them act as excellent drug delivery nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomicelles are classified into three key distinct nanosystems i.e., colloidal nanomicelles formulated from an aggregation of polar and nonpolar molecules in an aqueous solution (amphiphilic aggregates), polyionic nanomicelles formulated from oppositely charged polymers generating an agglomeration due to electrostatic interaction, and nanomicelles originating from metal complexation [63][64][65][66].…”
Section: Classification Of Nanomicellesmentioning
confidence: 99%